Ответ:
x₁=0 x₂=
Объяснение:
-3(x+2)²=-2(x+6) умножаем обе стороны на (-1)
3(x+2)²=2(x+6)
по формуле(a+b)²=a²+2ab+b²
3(x²+4x+4)=2x+12
3x²+12x+12=2x+12
3x²+12x-2x+12-12=0
3x²+10x=0
x(3x+10)=0 3x+10=0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
x₁=0 x₂=![-\frac{10}{3} -\frac{10}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B10%7D%7B3%7D)
Объяснение:
-3(x+2)²=-2(x+6) умножаем обе стороны на (-1)
3(x+2)²=2(x+6)
по формуле(a+b)²=a²+2ab+b²
3(x²+4x+4)=2x+12
3x²+12x+12=2x+12
3x²+12x-2x+12-12=0
3x²+10x=0
x(3x+10)=0 3x+10=0
x₁=0 x₂=![-\frac{10}{3} -\frac{10}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B10%7D%7B3%7D)